OP0102 Presence of tophi and high level hyperuricemia are associated with increased risk of mortalty in patients with gout. (23rd January 2014) - Perez-Ruiz, F.; Martinez-Indart, L.; Pijoan, J.I.; Herrero-Beites, A.M.; Krisnan, E.; Carmona, L.
Abstract : Background: Several studies have linked gout with increased risk of cardiovascular events and mortality. There is no study linking severity of gout with mortality, as specific clinical evaluation of gout is nor currently available in databases. Objectives: To evaluate whether variables of severity of gout, such as number of flares, extent of joint involvement, tophaceous deposition, and radiology, are independently associated to increased risk of mortality. Methods: Prospective observational study of a cohort of 706 patients with gout from 1992 to 2008. Survival analysis was performed (bivariate Kaplan-Meier to select associated variable and then multivariate Cox proportional hazard analysis to ascertain variables independently associated with death as outcome) to ascertain an association between gout severity variable, cardiovascular risk factors, and other clinical variables with mortality. Standardized mortality rates (SMRs) were calculated to evaluate the magnitude of excess of mortality in patients with gout compared with that of the reference general regional population available for 2005. Results: Patients had crystal-based diagnosis of gout in 82% and a mean follow-up was 47 months. Subcutaneous tophi were present in 30.5%, >4 joints ever affected in 34.6%, the mean number of flares during the year previous to first evaluation was 3.4 per patient-yr, hypertension was present in 41.2%, hyperlipidemia in 42.2%, diabetes in 20.1%, and chronic renal disease (CKD<2) in 26.6%. Sixty four patients (9.1%) died during the observation period, a plausible cardiovascular cause being attributed to 38 (59%) of them. SMRs for patients with gout were 2.37 (95%CI limits 1.82-3.03), 1.57 (1.18- 2.05), and 4.50 (2.06-8.54) overall, for men, and for women respectively. Out of 13 variables possibly associated to mortality in bivariate analysis, the presence of subcutaneous tophi (Adjusted Hazard Risk 1.99, 1.25-3.20) and baseline serum urate level (AHR 1.17, 1.03-1.32 per mg/dl increase)were independently associated with higher risk of mortality, along with loop diuretic prescription (AHR 1, 98, 1.11-3.51), a history of previous vascular event (AHR 2.32, 1.27-4.35), and age (AHR 1.08, 1.05-1.11 per year increase). A further analysis showed that only the two highest quartiles of baseline serum urate (520 mcmol/L) were associated with an increased risk of mortality (AHR 2.44, 1.14-5.23 and 2.93, 1.41-6.08 respectively). Conclusions: The highest level of hyperuricemia and presence of tophi were associated to increased risk of mortality, of cardiovascular cause in most cases, in patients with gout. Avoiding delay of treatment until patients suffer severe gout seems to be judicious. Disclosure of Interest: F. Perez-Ruiz Grant/Research support from: Ministerio de Sanidad, Gobierno de España, Consultant for: Menarini, Novartis, Savient, Ardea, Speakers Bureau: Menarini, Novartis, Ardea, L. Martinez-Indart: None Declared, J. Pijoan: None Declared, A. Herrero-Beites: None Declared, E. Krisnan: None Declared, L. Carmona Speakers Bureau: Menarini